Mentoring Activities of Digital Startup Competition “Samarinda Hackathon” Towards SMART Ibu Kota Nusantara - Almasari Aksenta; Prapdopo Prapdopo (Journal of Community Development, 2024)
Business and economic growth in a region is supported by digital transformation. Many people are switching to using digital technology to support their business activities. Thus, the opportunity to create digital-based business ideas or what is known as a startup business was born. The Samarinda City Communication and Informatics Agency held a digital startup competition called Samarinda Hackathon in order to support digitalization for regional growth, especially by supporting the development of the capital city of Indonesia (Ibu Kota Nusantara). In the competition, there were mentoring activities as an effort to assist participants' education and from this activity process, it is hoped that it will have sustainable benefits. Participants not only apply it to this competition but can also build a real business. In addition, this activity is also related to one of the pillars of Indonesia Emas 2045, namely having superior human resources. This activity lasted for 2 days in the city of Samarinda. The mentoring activity was carried out by 12 mentors affiliated with the Samarinda City Communication and Information Office, the 1000 Digital Startup community, East Kalimantan ICT Volunteers, academics, and several practitioners. The mentoring activity began with a presentation of material by digital startup CEOs, a question and answer session, then a participant mentoring session by creating a sprint design, and conducting a consultation session. The results or achievements of the mentoring activities carried out can be seen in the participants who can create sprint designs that are more focused and conceptual as startup business designs and the enthusiasm of the participants which can be seen after receiving motivation and various suggestions from the mentors.